What’s new in COPD? - Śliwiński, Paweł (Przewodnik Lekarza/Guide for GPs, 2006)
Results of clinical studies conducted in patients with chronic obstructive pulmonary disease (COPD) in recent years have pointed out at new perspectives in the management of COPD. They include both pharmacological and non-pharmacological methods. Progress in pharmacological therapy results mainly due to introduction of long acting anticholinergic compound and combined therapy with long acting β 2 -agonists and inhaled corticosteroids. Non-invasive positive pressure ventilation (NIPPV) appears to play a significant role in the treatment of severe COPD exacerbations. Also pulmonary rehabilitation has found very important position in the management of COPD patients. However, from patients’ perspective the most important benefit resulting from new therapies is an improvement in health related quality of live.